Diagnostic Utility of a Ferritin-to-Procalcitonin Ratio to Differentiate Patients With COVID-19 From Those With Bacterial Pneumonia: A Multicenter Study. (14th March 2021) - Gharamti, Amal A; Mei, Fei; Jankousky, Katherine C; Huang, Jin; Hyson, Peter; Chastain, Daniel B; Fan, Jiawei; Osae, Sharmon; Zhang, Wayne W; Montoya, José G; Erlandson, Kristine M; Scherger, Sias J; et al.
Abstract: Background: There is an urgent need for accurate, rapid, inexpensive biomarkers that can differentiate coronavirus disease 2019 (COVID-19) from bacterial pneumonia. We assess the role of the ferritin-to-procalcitonin (F/P) ratio to classify pneumonia cases into those due to COVID-19 vs those due to bacterial pathogens. Methods: This multicenter case–control study compared patients with COVID-19 with those with bacterial pneumonia, admitted between March 1 and May 31, 2020. Patients with COVID-19 and bacterial pneumonia co-infection were excluded. The F/P in patients with COVID-19 vs with bacterial pneumonia were compared. Receiver operating characteristic curve analysis determined the sensitivity and specificity of various cutoff F/P values for COVID-19 vs bacterial pneumonia. Results: A total of 242 COVID-19 pneumonia cases and 34 bacterial pneumonia controls were included. Patients with COVID-19 pneumonia had a lower mean age (57.1 vs 64.4 years; P = .02) and a higher body mass index (30.74 vs 27.15 kg/m 2 ; P = .02) compared with patients with bacterial pneumonia. Cases and controls had a similar proportion of women (47% vs 53%; P = .5), and COVID-19 patients had a higher prevalence of diabetes mellitus (32.6% vs 12%; P = .01). The median F/P was significantly higher in patients with COVID-19 (4037.5) compared with the F/P in bacterial pneumonia (802; P < .001). An F/P ≥877, used to diagnose COVID-19, resulted in a sensitivity of 85% and a specificity of 56%, with a positive predictive value of 93.2% and a likelihood ratio of 1.92. In multivariable analyses, an F/P ≥877 was associated with greater odds of identifying a COVID-19 case (odds ratio, 11.27; 95% CI, 4–31.2; P < .001). Conclusions: An F/P ≥877 increases the likelihood of COVID-19 pneumonia compared with bacterial pneumonia.